Effectiveness of Oxygen and Other Acute Treatments for Cluster Headache: Results From the Cluster Headache Questionnaire, an International Survey - Pearson, Stuart M.; Burish, Mark J.; Shapiro, Robert E.; Yan, Yuanqing; Schor, Larry I. (Headache, 2019)
Objective To assess the effectiveness and adverse effects of acute cluster headache medications in a large international sample, including recommended treatments such as oxygen, commonly used medications such as opioids, and emerging medications such as intranasal ketamine. Particular focus is paid to a large subset of respondents 65 years of age or older. Background Large international surveys of cluster headache are rare, as are examinations of treatments and side effects in older cluster headache patients. This article presents data from the Cluster Headache Questionnaire, with respondents from over 50 countries and with the vast majority from the United States, the United Kingdom, and Canada. Methods This internet‐based survey included questions on cluster headache diagnostic criteria, which were used as part of the inclusion/exclusion criteria for the study, as well as effectiveness of medications, physical and medical complications, psychological and emotional complications, mood scores, and difficulty obtaining medications. The diagnostic questions were also used to create a separate group of respondents with probable cluster headache. Limitations to the methods include the use of nonvalidated questions, the lack of a formal clinical diagnosis of cluster headache, and the grouping of some medications (eg, all triptans as opposed to sumatriptan subcutaneous alone). Results A total of 3251 subjects participated in the questionnaire, and 2193 respondents met criteria for this study (1604 cluster headache and 589 probable cluster headache). Of the respondents with cluster headache, 68.8% (1104/1604) were male and 78.0% (1245/1596) had episodic cluster headache. Over half of respondents reported complete or very effective treatment for triptans (54%, 639/1139) and oxygen (54%, 582/1082). Between 14 and 25% of respondents reported complete or very effective treatment for ergot derivatives (dihydroergotamine 25%, 42/170; cafergot/ergotamine 17%, 50/303), caffeine and energy drinks (17%, 7/41), and intranasal ketamine (14%, 5/37). Less than 10% reported complete or very effective treatment for opioids (6%, 30/541), intranasal capsaicin (5%, 7/151), and intranasal lidocaine (2%, 5/241). Adverse events were especially low for oxygen (no or minimal physical and medical complications 99%, 1077/1093; no or minimal psychological and emotional complications 97%, 1065/1093), intranasal lidocaine (no or minimal physical and medical complications 97%, 248/257; no or minimal psychological and emotional complications 98%, 251/257), intranasal ketamine (no or minimal physical and medical complications 95%, 38/40; no or minimal psychological and emotional complications 98%, 39/40), intranasal capsaicin (no or minimal physical and medical complications 91%, 145/159; no or minimal psychological and emotional complications 94%, 150/159), and caffeine and energy drinks (no or minimal physical and medical complications 89%, 39/44; no or minimal psychological and emotional complications 91%, 40/44). This is in comparison to ergotamine/cafergot (no or minimal physical and medical complications 83%, 273/327; no or minimal psychological and emotional complications 89%, 290/327), dihydroergotamine (no or minimal physical and medical complications 81%, 143/176; no or minimal psychological and emotional complications 91%, 160/176), opioids (no or minimal physical and medical complications 76%, 416/549; no or minimal psychological and emotional complications 77%, 423/549), or triptans (no or minimal physical and medical complications 73%, 883/1218; no or minimal psychological and emotional complications 85%, 1032/1218). A total of 139 of 1604 cluster headache respondents (8.7%) were age 65 and older and reported similar effectiveness and adverse events to the general population. The 589 respondents with probable cluster headache reported similar medication effectiveness to respondents with a full diagnosis of cluster headache. Conclusions Oxygen is reported by survey respondents to be a highly effective treatment with few complications in cluster headache in a large international sample, including those 65 years or over. Triptans are also very effective with some side effects, and newer medications deserve additional study. Patients with probable cluster headache may respond similarly to acute medications as patients with a full diagnosis of cluster headache.